A case report of comprehensive treatment for primary intraspinal carcinosarcoma - Yan, Chang; Zhang, Chao-Jun; Wei, Jun-bao; Liang, Hui-wen; Qu, Song (Frontiers in Oncology, 2025)
BackgroundCarcinosarcoma is a rare and highly aggressive biphasic malignant tumor. To date, no cases of primary intraspinal carcinosarcoma have been reported.Case presentationThis study reports a case of a 36-year-old female with primary intra dural extramedullary carcinosarcoma. The patient underwent surgery at initial diagnosis, followed by two courses of radiotherapy due to residual tumor, as part of a comprehensive antitumor treatment. Despite good tumor control, she ultimately died of respiratory failure.DiscussionThis is the first reported case of primary intra dural extramedullary carcinosarcoma, detailing its imaging characteristics, pathological morphology, and treatment process. The tumor was responsive to radiotherapy. The rapid progression of intraspinal carcinosarcoma suggests it may be underdiagnosed or underreported, highlighting the need for more cases for clinical evaluation and treatment strategies.